Fluidized bed bioreactor for multiple environmental engineering solutions - Ozkaya, Bestami; Kaksonen, Anna H.; Sahinkaya, Erkan; Puhakka, Jaakko A. (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
Fluidized bed bioreactors (FBR) are characterized by two-phase mixture of fluid and solid, in which the bed of solid particles is fluidized by means of downward or upward recirculation stream. FBRs are widely used for multiple environmental engineering solutions, such as wastewater treatment, as well as some industrial applications. FBR offers many benefits such as compact bioreactor size due to short hydraulic retention time, long biomass retention on the carrier, high conversion rates due to fully mixed conditions and consequently high mass transfer rates, no channelling of flow, dilution of influent concentrations due to recycle flow, suitability for enrichment of microbes with low Km values. The disadvantages of FBRs include bioreactor size limitations due to the height-to-diameter ratio, high-energy requirements due to high recycle ratios, and long start-up period for biofilm formation. This paper critically reviews some of the key studies on biomass enrichment via immobilisation of low growth yield microorganisms, high rates via fully mixed conditions, technical developments in FBRs and ways of overcoming toxic effects via solution recycling. This technology has many potential new uses as well as hydrodynamic characteristics, which enable high-rate environmental engineering and industrial applications. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: Biofilm; Fluidized bed bioreactor; High rate; Water treatment; Wastewater treatment; WASTE-WATER TREATMENT; INVERSE TURBULENT BED; ANAEROBIC MEMBRANE BIOREACTOR; FERRIPHILUM-DOMINATED BIOFILM; FERROUS SULFATE OXIDATION; GRANULAR ACTIVATED CARBON; HYDROGEN-PRODUCTION; IRON OXIDATION; AUTOTROPHIC DENITRIFICATION; BIOHYDROGEN PRODUCTION; Engineering; Environmental Sciences & Ecology; Water Resources